Household-related stress, intimate partner violence and mental health: exploring the syndemic in urban slum women in Bangladesh during Covid-19 pandemic - Kamrun Nahar Koly; Rasma Muzaffar; Zinnatun Nessa; Arif Billah; Sabrina Rasheed; Anuj Kapilashrami (International Journal for Equity in Health)
Abstract Introduction Mental health conditions are emerging concerns that were worsened by Covid-19, especially in developing countries. The pandemic instigated an increase in household stress particularly among migrant women living in urban slums due to overcrowding, increased caregiving burden, and intimate partner violence, resulting in deteriorating mental health. This study assessed the prevalence of mental health conditions and intimate partner violence during Covid-19 and also explored the pathways between pandemic-related household stress and mental health outcomes with the mediating role of crowding and intimate partner violence in the Bangladeshi urban slums. Method The cross-sectional survey was conducted among internal migrant women from five slums of Urban Health and Demographic Surveillance Systems operated by International Centre for Diarrhoeal Disease Research, Bangladesh. Face-to-face interviews were conducted from August to October 2022 using a semi-structured questionnaire that had three validated screening tools to measure depression, anxiety and intimate partner violence. A path analysis using structural equation modelling with maximum likelihood methods was performed to understand the objectives. Result Among the total 405 participants, the majority of women (68.40%) were housewives and their husbands (46.43%), were engaged as daily wagers. A large portion of the women (38.77%) had only primary education and one-third of the surveyed women (36.5%) reported increased household stress due to Covid-19. About 71% of women experienced an event of intimate partner violence with reports of emotional (57.3%), physical (49.4%), and sexual violence (39.0%). The prevalence of anxiety and depression were 73.8% and 65.2%, respectively. The structural equation modelling path analysis revealed that household stress increased the likelihood of anxiety and depression. Moreover, household stress has a direct effect on anxiety, while it has an indirect effect on both anxiety and depression with these effects mediated by intimate partner violence. Conclusion These novel baseline findings may support the relevant stakeholders to design further research and programmes to strengthen emergency preparedness for the women living in informal settlements of Urban Bangladesh. A rights-based approach, as has been shown effective elsewhere, may offer a strategy to enhance the overall well-being.